Marketing Strategy for Welding Workshops in the New Normal Era after the Covid-19 Pandemic - Andika Isma; Andi Hidayatullah; Agung Winarno; Agus Hermawan (Universitas Negeri Makassar, 2020)
The Covid-19 pandemic has a major impact on all aspects and sectors of public life, especially business actors. The impact of the Covid-19 Pandemic was also experienced by welding workshops, one of which was the Barakka Las workshop. This study aims to determine the implementation of marketing strategies in the welding workshop business